Hyflex CM and EDM from Shape Memory to Control Memory. - Jamal A. Abu Al‑Timan; Iman M. Al‑Zaka; Baidaa M. Zeidan (Erbil Dental Journal)
The new era in endodontics has been established with the introduction of nickel titanium (NiTi) alloys, and later on the automation of mechanical preparation. By changing the phase transformation temperatures of NiTi alloy, the manufacturers alter the phase composition to have a NiTi with new mechanical properties. These mechanical properties can be achieved either by thermal, mechanical treatments or both. Moreover, many machining procedures (e.g. twisting, electrical discharge machining), were developed. The higher flexibility of thermomechanically treated NiTi alloys was found as the main advantages of these alloys with the improvement of cyclic fatigue resistance when compared to conventional NiTi. Austenitic alloys have superelastic properties due to stress-induced martensite transformation and consequently try to springback to their original shape after distortion. In contrast, the martensitic instruments have ability to reorientation of martensite variants when heated. So these instruments easily deformed and show a shape memory effect. Moreover, the use of martensitic alloy results in more flexible files, with an increased cyclic fatigue resistance compared with austenitic alloy. So, continued development in the manufacturing treatment of NiTi alloys has resulted in the producing of controlled memory (CM) wire. These materials do not possess superelastic properties at neither room nor body temperature. This article reviews the development process, features and properties of Hyflex file and Hyflex EDM file made from CM wire.